Pemberdayaan Jemaat Sebagai Strategi Gereja dalam Mempersiapkan Guru Sekolah sebagai Generasi Penerus di Era Digitalisasi - Eben Munthe (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2022)
Abstract: The teacher is a very noble profession and plays an important role in preparing a future generation, especially in the digitalization era so that the church in carrying out the Great Commission of Christ, which is to make all nations become disciples of Jesus, has a responsibility to empower existing resources, namely the congregation as one of the strategies that can be implemented. the church is doing in preparing the congregation as school teachers so that they can educate students as the next generation of the church in particular and the next generation of the Indonesian nation in this digitalization era so that later they can be useful for the nation and state and the church. The writing methods used are qualitative research methods and library research, namely collecting materials from various sources such as books, articles and other reading materials that can be used as references for writing this article.Abstrak: Frofesi seorang Guru adalah sangat mulia dan sangat berperan penting dalam mempersiapkan sebuah generasi mendatang terutama di era digitalisi sehingga gereja dalam melaksanakan Amanat AgungNya yaitu menjadikan semua bangsa menjadi murid Yesus memiliki tanggung jawab dalam memberdayakan sumber daya yang ada yaitu jemaat sebagai salah satu strategi yang gereja lakukan dalam mempersiapkan jemaat sebagai guru sekolah sehingga dapat mendidik murid-murid sebagai generasi Penerus gereja pada khususnya dan generasi penerus bangsa Indonesia di era digitalisasi ini sehingga kelak mereka bermanfaat bagi bangsa dan negara serta gereja. Metode penulisan yang digunakan ialah metode penelitian kualitatif dan perpustakaan (library research) yaitu mengumpulkan dari berbagai sumber seperti buku-buku, artikel-artikel dan bahan-bahan bacaan lainnya yang dapat dijadikan referensi bagi penulisan artikel ini.